2006
DOI: 10.1007/s11064-005-9034-2
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Activates Protein Kinase B (PKB/Akt) through AMPA Receptors in Cultured Bergmann Glia Cells

Abstract: Glutamate is involved in gene expression regulation in neurons and glial cells through the activation of a diverse array of signaling cascades. In Bergmann glia, Ca2+ -permeable alpha-hydroxy-5-methyl-4-isoazole-propionic acid (AMPA) receptors become tyrosine phosphorylated after ligand binding and by these means form multiprotein signaling complexes. Of the various proteins that associate to these receptors, the phosphatidylinositol 3-kinase (PI-3K) deserves special attention since D3-phosphorylated phosphoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…We have previously reported that nicotinic acetylcholine receptor stimulation also protects neurons against glutamate through the PI3K‐Akt system (Kihara et al, 2001). Stimulation of AMPA receptors activates the PI3K‐Akt system via Src (Morales et al, 2006). It has been reported that AMPA protects neurons against glutamate excitotoxicity through PI3K activation (Wu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that nicotinic acetylcholine receptor stimulation also protects neurons against glutamate through the PI3K‐Akt system (Kihara et al, 2001). Stimulation of AMPA receptors activates the PI3K‐Akt system via Src (Morales et al, 2006). It has been reported that AMPA protects neurons against glutamate excitotoxicity through PI3K activation (Wu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…[535593] Several key processes seem to be involved and include PTEN, NF-κB, Akt, and calpain2, all of which are linked to glutamate receptors, either directly or indirectly. [45355848590]…”
Section: Glutamate-induced Cell Signaling and Glioma Invasionmentioning
confidence: 99%
“…[46] Akt expression is linked to NF-κB activation, which is in turn activated by glutamate. [5684] The latter observation provides a link between inflammation, glutamate receptor activation (immunoexcitotoxicity), and tumor invasion and aggressiveness.…”
Section: Glutamate-induced Cell Signaling and Glioma Invasionmentioning
confidence: 99%
“…Glutamate has been shown to activate AKT through the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor in glial cells 62 and glioblastoma cells, 63 a process that may lead to invasive growth and anaplasia in tumor cells. In addition to AMPA receptor involvement, N-methyl-D-aspartic acid (NMDA) receptor stimulation leads to AKT activation in a PI3K-dependent manner, 64 and this activation results in cell death which is necrotic in nature.…”
Section: Phosphatase and Tensin Homolog (Pten) And Aktmentioning
confidence: 99%